Sustainable urban development through increased construction in wood? - Sjöström, Fredrik (2018)
The increased awareness of the construction industry's impact on the global climate combined with the current housing shortage in Sweden has contributed to an increasing ask for more wood in construction amongst stakeholders, municipalities and politicians. In order to meet Sweden's climate goals it is necessary that new materials, technologies and working methods continue to evolve. Knowledge, cooperation and communication are described as important elements in order to develop the work towards increased sustainability in the construction sector in Sweden. Through different forms of cooperation, knowledge and risk can be spread between the involved actors in large capital-intensive construction projects while the construction process tends to be streamlined and life cycle costs minimized.